Effects of substrate and salinity in hydroponically grown Cichorium spinosum - Klados, E.; Tzortzakis, Nikos G. (My University, 2014)
The present work, examined the effect of salinity (5, 40 and 120 mmol L-1 NaCl) in the growth and the quality of hydroponic culture of stamnagathi (Cichorium spinosum L.). Plants were developed in perlite, pumice, rockwool and sand respectively. High salinity decreased leaf number, leaf size and plant biomass in plants grown in perlite, pumice and sand. Reduced plant biomass also observed in plant grown in rockwool, although an increased number of leaves were produced. Leaf area reduced in plants grown in rockwool and sand under 120 mmol L-1 NaCl. Low salinity maintained almost similar status as the control treatments. Symptoms of tip burn appeared in 120 mmol L-1 NaCl treated stamnagathi for perlite and pumice. No differences observed in leaf chlorophyll content, leaf fluorescence and in symptoms of discoloration. When the perlite was used as substrate, salinity increased total phenols and decreased protein content. Finally, the low concentration of salinity improved some plant quality parameters as recorded by panelists, following organoleptic test. Thus, stamnagathi proved to successfully tolerate low salinity concentration in hydroponically grown plants.
Keywords: Agronomic performance; Growth; Salt stress; Soilless culture; Stamnagkathi